Singapore's investment abroad - Lim, Celine Ai Ping (2015)
The recent surge in local investments overseas as well as the government's increasing concern in promoting such overseas investment have generated much interest in this area. Despite this growing significance in DFI overseas, little research has been done on the factors that motivate Singapore firms to venture abroad and on the impact of DFI on the Singapore economy. The report attempts to study the theories behind the motivations of DFI, the factors taken into consideration by the Singaporean investors when deciding to undertake DFI abroad, the costs and benefits ofDFI to the Singapore economy, and the government incentives available to investors to encourage them to invest overseas. Our study reviews the four main theories of DFI. These are the oligopolistic theory, location-specific theory, intemalisation theory, and the eclectic theory. The theories are applied to the motivations behind Singaporean investors participating in DFI abroad. The factors encouraging DFI abroad can be divided into push and pull factors. Some push factors include, to avoid high labour costs and to extend current business operations, while pull factors include the availability of cheaper labour and land and, the availability if technology and expertise. In addition, our report highlights the impediments to DFI abroad, one of which is the difficulty in recruiting suitable staff for the overseas venture. Our study also covers the costs and benefits of DFI abroad to the Singapore economy. If DFI is simply a relocation of operations to foreign countries with no direct linkages to the Singapore economy, DFI would be a cost to the economy. It would constitute a "capital flight" as the immediate effect would be a capital transfer of funds overseas. On the other hand, if the profits of these investments were to be remitted back to Singapore, it would contribute to our GNP. In addition, these revenues remitted to Singapore will be subjected to tax and the government can use this tax revenue to provide better infrastructure. Moreover, the foreign operations may want to source their inputs from the Singapore companies. These creates additional business opportunities to the Singapore economy. The government has a role to play in increasing DFI overseas by providing incentives to encourage the investors to go abroad. In addition, these schemes should aim to encourage the creation of benefits to the Singapore economy. An example of such incentive is the Double Taxation Relief. This allows the investors to remit their foreign sourced income without being taxed in both countries, thus encouraging the remittance of income. Other incentives can include the provision of infrastructural developments, the organisation of business forums, and the Local Enterprise Finance Scheme.